Light and pH-activated nanoplatform based on oxidative stress-amplified for photodynamic and ferroptosis synergistic therapy of breast cancer - Song Li; Zhenxin Guan; Yurong Liu; Xiaokang Zhang; Yunheng Liu; Shaojing Jiang; Wenjing Liu; Aoya Wang; Xiaolin Li; Xukai Che; Liyuan Shao; Li Zhang; et al. (Materials & Design)
Compared to traditional tumor chemotherapy, photodynamic therapy (PDT) can effectively reduce toxic side effects and prevent tumor resistance. However, the reactive oxygen species (ROS) generated by photosensitizers are limited, and the destructive effects on tumor cells are inadequate. In this study, nanomedicines loaded with the photosensitizers chlorin e6 (Ce6) and dihydroartemisinin (DHA) were constructed using human serum albumin (HSA) and transferrin (Tf), self-assembly for the programmed activation, and expansion of ROS in tumor cells. These nanomedicines, Ce6/DHA@HSA-SS-Tf nanoparticles (NPs), can target Tf receptors overexpressed on cancer cells to produce ROS through PDT with laser irradiation. Subsequently, the ROS-responsive vector is cleaved, and iron ions catalyze the released DHA to produce sufficient ROS and induce ferroptosis in tumor cells. The nanomedicine amplifies the ROS content in tumor cells through a dual response and programmed activation, which can effectively solve the problem of insufficient ROS production in tumor PDT. Consequently, the Ce6/DHA@HSA-SS-Tf NPs demonstrate excellent anti-tumor effects through the synergistic effects of PDT and ferroptosis. This treatment strategy provides a reliable basis for tumor-specific and efficient treatments.